Heart of Borneo Series 7 : Tama Abu – Where the Beat Becomes Rhythm - Kalu, Meekiong (Forest Department Sarawak, 2020)
This book is the seventh in the Heart of Borneo Series, publication under the Heart of Borneo Initiative for Sarawak. It gives us a sight on the findings of the Scientific Expedition to Tama Abu Production Forest in 2017, which organized by the Forest Department Sarawak.